Recombinant human hyaluronidase facilitated subcutaneous immunoglobulin treatment in pediatric patients with primary immunodeficiencies: long-term efficacy, safety and tolerability. (October 2016) - Wasserman, Richard L; Melamed, Isaac; Kobrynski, Lisa; Puck, Jennifer; Gupta, Sudhir; Doralt, Jennifer; Sharkhawy, Marlies; Engl, Werner; Leibl, Heinz; Gelmont, David; Yel, Leman
Aim: To assess the long-term efficacy, safety and tolerability of recombinant human hyaluronidase-facilitated subcutaneous infusion of immunoglobulin (Ig) (fSCIG; HYQVIA ® ; IGHy) in children aged <18 years.Patients & methods: Patients with primary immunodeficiency diseases were included in the studies. IGHy was administered every 3 or 4 weeks.Results: Validated acute serious bacterial infections were reported at 0.08/patient-year (four pneumonia episodes in three patients). No serious adverse drug reaction (ADR) was reported, and rates of local and systemic ADRs were low (0.09/infusion and 0.1/infusion). Infection rates were low (3.02/patient-year) with sustained Ig trough levels (median: 1009 mg/dl). Of 674 IGHy infusions, 97.2% required no change of administration due to ADR, in most (82.5%) with one infusion site. No patient developed neutralizing anti-rHuPH20 antibodies. Postpivotal study, 100% of patients aged <14 years or their caregivers and 85.7% of patients aged 14 to <18 years expressed preference for IGHy compared with Ig administered intravenously or Ig administered subcutaneously.Conclusion: These studies, with the longest (maximum: 3.3 years) duration of any reported Ig replacement trials in children with primary immunodeficiency diseases, showed low infection, local and systemic reaction rates along with well-tolerated infusions given in a single site.